Mixed infection of an emaravirus, a crinivirus, and a begomovirus in Pueraria lobata (Willd) Ohwi - Liang, Xiaofei; Mei, Shiqiang; Yu, Haodong; Zhang, Song; Wu, Jiaxing; Cao, Mengji (Frontiers in Microbiology, 2022)
Pueraria lobata (Willd) (Pueraria montana var. lobata (Willd.) Maesen & S. M. Almeida ex Sanjappa & Predeep) is an important herbal medicine used in many countries. In P. lobata plants showing symptoms of mosaic, yellow spots, and mottling, a mixed infection of new viruses provisionally named Pueraria lobata-associated emaravirus (PloAEV, genus Emaravirus), Pueraria lobata-associated crinivirus (PloACV, genus Crinivirus), and isolate CQ of the previously reported kudzu mosaic virus (KuMV-CQ, genus Begomovirus) was confirmed through high-throughput sequencing. PloAEV has five RNA segments, encoding a putative RNA-dependent RNA polymerase, glycoprotein precursor, nucleocapsid protein, movement protein, and P5, respectively. PloACV has two RNA segments, encoding 11 putative proteins. Only PloAEV could be mechanically transmitted from mixed infected symptomatic kudzu to Nicotiana benthamiana plants. All three viruses were detected in 35 symptomatic samples collected from five different growing areas, whereas no viruses were detected in 21 non-symptomatic plants, suggesting a high association between these three viruses. Thus, this study provides new knowledge on the diversity and molecular characteristics of viruses in P. lobata plants affected by the viral disease.